Genotype Heterogeneity in Accessions of a Winter Barley Core Collection Assessed on Postulated Specific Powdery Mildew Resistance Genes - Antonín Dreiseitl (Agronomy, 2021)
Gene bank accessions are necessary for implementing many research and breeding projects. However, a great number of accessions are contaminated or confused. If such accessions are used, the results obtained from these projects are inaccurate and non-reproducible. There are methods that allow almost perfect genotype identification; nevertheless, they are relatively recent and results cannot be compared with the characteristics of the original accessions. Growing resistant cultivars is an environmentally safe and cheap way of disease management and knowledge of diverse resistance genes and their combinations can be used to identify varieties and verify their authenticity and homogeneity. For this purpose, all 172 accessions of the core collection (CC) of the Czech winter barley (Hordeum vulgare) gene bank, originating from 35 countries, were studied. For resistance tests, 51 reference isolates of Blumeria graminis f. sp. Hordei, collected in all nonpolar continents over a period of 63 years and representing the global virulence/avirulence diversity of the pathogen, were used. Only 25 barley accessions were homogeneous (genetically uniform), whereas 147 accessions were heterogeneous due to presence of different genotypes. In total, 17 resistance genes were found singly or in combinations; 76.3% of accessions with identified resistance genes carried alleles at the Mla locus. To purify the CC, progenies of individual plants must be multiplied and authenticity and homogeneity of the seed should be confirmed with resistance tests, and subsequently can be studied with more advanced methods.